Tiwaripotamon keeae sp. nov. (Crustacea: Decapoda: Potamidae), a new miniature species of freshwater crab from the China-Vietnam border in Napo, Guangxi - Huang, Chao; Shih, Hsi-Te; Ahyong, Shane T. (Zootaxa, 2024)
A new miniature species of freshwater crab from the genus Tiwaripotamon Bott, 1970 (Potamidae), is described from a montane karst area in southern Napo, at the China-Vietnam border. It is the twelfth known species of the genus, and is also the smallest known, with the largest adult specimen observed barely exceeding 20 mm in carapace width. Apart from the small size, features of the eyes, carapace and ambulatory legs further set Tiwaripotamon keeae sp. nov. apart from its congeners. Pairwise genetic distances of the mitochondrial cytochrome oxidase subunit I (COI) gene also support it as a distinct species.